Different Physiological Roles of ATP- and PP(i)-Dependent Phosphofructokinase Isoenzymes in the Methylotrophic Actinomycete Amycolatopsis methanolica - Alves, A. M. C. R. (American Society for Microbiology, 2001)
Cells of the actinomycete Amycolatopsis methanolica grown on glucose possess only a single, exclusively PP(i)-dependent phosphofructokinase (PP(i)-PFK) (A. M. C. R. Alves, G. J. W. Euverink, H. J. Hektor, J. van der Vlag, W. Vrijbloed, D.H.A. Hondmann, J. Visser, and L. Dijkhuizen, J. Bacteriol. 176:6827–6835, 1994). When this methylotrophic bacterium is grown on one-carbon (C(1)) compounds (e.g., methanol), an ATP-dependent phosphofructokinase (ATP-PFK) activity is specifically induced, completely replacing the PP(i)-PFK. The two A. methanolica PFK isoenzymes have very distinct functions, namely, in the metabolism of C(6) and C(1) carbon substrates. This is the first report providing biochemical evidence for the presence and physiological roles of PP(i)-PFK and ATP-PFK isoenzymes in a bacterium. The novel ATP-PFK enzyme was purified to homogeneity and characterized in detail at the biochemical and molecular levels. The A. methanolica ATP-PFK and PP(i)-PFK proteins possess a low level of amino acid sequence similarity (24%), clearly showing that the two proteins are not the result of a gene duplication event. PP(i)-PFK is closely related to other (putative) actinomycete PFK enzymes. Surprisingly, the A. methanolica ATP-PFK is most similar to ATP-PFK from the protozoon Trypanosoma brucei and PP(i)-PFK proteins from the bacteria Borrelia burgdorferi and Treponema pallidum, both spirochetes, very distinct from actinomycetes. The data thus suggest that A. methanolica obtained the ATP-PFK-encoding gene via a lateral gene transfer event.